Aplicación de un plan de contingencia para la recuperación de la cartera de crédito en la Cooperativa de Ahorro y Crédito “Coorcotopaxi” ltda., ubicado en el cantón Latacunga, provincia de Cotopaxi, durante el período 2014 - Alomoto Masaquiza, Ana Luz (2015)
The present research work has information about the Contingency Plan in order to improve the policies, processes and lending standards to reduce the arrears loans in the credit union "COORCOTOPAXI" Ltda. For the application of a Contingency Plan, It was considered useful to analyze the internal and external factors that influence within the institution, to do a situational study of the institution was made by appropriate researching through which relevant information is obtained for proper decision making….